Multi Agent System (MAS) for bus driver duty reassignment in the event of late for Second Piece of Work (LSPW) - Mansor, Nur Farraliza; Shibghatullah, Abdul Samad; Amir Hussin, Amir Aatieff; Chit, Su Mon; Eldabi, Tillal (IOP Publishing Ltd., 2020)
Unforeseen (abrupt, sudden, unanticipated, unexpected) incidents (UI) are events that occurs without notice causing interruptions to public transport services. In the operation of bus services, one of the sources of UI are bus drivers. For example, if a bus driver comes late for his/her duty it delays scheduled departures thereby causing a ripple effect on the entire schedule. There are three types of driver lateness that are; Late for First Work (LFFW), Late for Break (LFB), and Late for Second Piece of Work (LSPW). This paper will only discuss the possible solution for a LSPW event. When a LSPW happen, the predefined schedule remains the same however the duty needs to be reassigned to another driver that is available. Currently, a supervisor at the bus depot uses a manual way to complete duty reassignment and there are no automated ways of reassignment. Manual duty reassignments are slow and prone to errors. The objective of this paper is to propose an automated duty reassignment in the event of a LSPW using Multi-Agent System (MAS). MAS is dynamic, able to adapt to varying situations and quick at finding solutions through negotiation and collaboration between the agents. Experiment were conducted using the AgentPower simulation tool. The results concluded that the proposed technique is effective for duty reassignment in the event of LSPW.